Probiotic bacteria in prevention and treatment of diarrhea - Jasmina Havranek; Šimun Zamberlin; Iva Dolenčić Špehar; Tamara Prtilo; Milna Tudor; Dubravka Samaržija (Mljekarstvo)
Probiotic bacteria have beneficial effects in prevention and treatment of different diseases. The results of preventive and therapeutic effect of probiotic bacteria on diarrhea during last ten years are shown in this paper. The greatest preventive and therapeutic effect of probiotic bacteria was identified for acute diarrhea in children caused by rotaviruses. Significant, but slightly lower effect of probiotic bacteria was proved for antibiotic associated diarrhea. Positive effect in prevention of traveller’s diarrhea and radiation-induced diarrhea is not significant. Preventive and therapeutic effect on diarrhea is not dependent on the way of probiotic bacteria consumption, by fermented milk, capsule or oral rehydration solution.